Teaching the Principle Jacobi Method Using MATLAB (Sebha University Conference Proceedings, 2025)
This paper presents a study of the effectiveness of the MATLAB program in solving linear equations using iteration methods for numerical analysis, as the numerical analysis of some linear equations requires many complex operations to analyse the approximate solutions, and this leads to many computational errors, and great effort to solve them. The importance of this study lies in shedding light on the MATLAB program and its strength in solving linear equation problems and helping students solve complex equations faster and more accurately. The aim of this study is to know one of the iterative methods represented by the Jacobi method, to solve systems of linear equations, using the MATLAB program to calculate the values, where the solution is done by guessing a specific solution, which is improved in successive steps until the results become close with the progress of the steps, which is the final solution for a set of linear equations, as we changed the error value by adding and subtracting 50%, and we noticed an increase in the number of iterations and a decrease in the error, which led to obtaining satisfactory results.